KAUSALITAS GRANGER PDRB TERHADAP KESEMPATAN KERJA DI PROVINSI DATI I JAWA TENGAH - Soebagiyo, Daryono (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
This research conducted to know the relation of causality between Regional Gross Domestic Products (PDRB) and level of employment. Research method which applied is Granger causality test. Then to get estimation result, done testing stationerity, integration degree testing by using ADF (Augmented Dickey Fuller), and testing cointegration by using ADF. Data in the research is time series data from year 1979 up to 2004. Analysis result gives conclusion that found unidirectional causality relation from Regional Gross Domestic Product (PDRB) to employment level.